A three-dimensional simulation method of ground cracks based on images from drone. Issue 7 (April 2020) - Yajun, Lei; Ao, Zhang; Jianhui, Yang; Wangxin, Cheng; Zhanling, Sun; Shasha, Xia; Ting, Zhou; Lihong, Dong
Abstract: The ground cracks in the goaf will affect the safety of the local people and the ecological environment. Therefore, the three-dimensional model of the ground cracks can provide certain decision support for the coal mine safety production managers. In this paper, a three-dimensional model method for ground cracks based on images acquired by drones is proposed. Firstly, based on a small amount of original borehole data, Kriging interpolation method is used to generate enough stratum information, and the grid model is used to establish the original stratum three-dimensional model. Secondly, the image acquired by the drone is needs to be preprocessed, and the corner data is obtained as the key point of the crack by using the Harris algorithm. Thirdly, generate the three-dimensional model of the ground crack. It is inserted into the original three-dimensional model of the original stratum, and finally a three-dimensional model of the stratum containing the ground crack is obtained. The experimental verification shows that the method can effectively simulate the ground crack.